Potential of turmeric cream (curcuma caesia roxb.) extract in incision wounds - Udayani, Ni Nyoman Wahyu; Adrianta, I Ketut Agus; Wiguna, I Putu Bagus Artha; Yowani, Anak Agung Sagung Iswarani (Universitas Muhammadiyah Purwokerto, 2025)
Background: Incisional wounds are the most common wounds in the community. Improper handling of incision wounds can worsen wounds and cause infection. The content of secondary metabolites in black turmeric rhizomes can act as anti-inflammatory and antimicrobial in the healing process of incision wounds. However, its effectiveness in healing incision wounds has not been widely studied, so further research is needed.Purpose: This study was conducted to determine the potential of black turmeric cream as an herbal medicine to heal incision wounds.Methods: This study was an invivo experimental research study with a randomized post-test control group design. The samples used were 20 male rats that were made to have a 2 cm incision wound on the back area, consisting of a negative control, a positive control, and three black turmeric extract groups (5%, 10%, and 15%). The data obtained were analyzed by an ANOVA (Analysis of Variance) parametric statistical test.Result: The results showed that the highest decrease in incision wound length was found in the black turmeric rhizome cream Formula III group and the lowest in the negative control group. On day 14, the incision wound area of the Formula III black turmeric rhizome cream group had closed or healed (0.00 cm), while the negative control group had the slowest incision wound closure (0.39 cm).Conclusion: Black turmeric rhizome cream can heal and prevent infection of the incision wound. This shows the potential of black turmeric rhizome as an anti-inflammatory and antimicrobial.